Study of tactics and personal security measures of the dialogue police during the protection of public order at mass events - O. A. Morhunov; I. V. Vlasenko (Law and Safety)
Further reform of law enforcement activities in Ukraine is, of course, absolutely necessary and requires constant attention from the leadership of the Ministry of Internal Affairs, the National Police and the services and units involved in this activity. The scientific approach and the definition of new directions and technologies are impossible without the use of research studies of the scientific and pedagogical staff of higher education institutions with specific learning conditions. The article analyzes the work of the dialogue police, identifies directions for improving their activities in terms of serving at mass events. Dialogue police is one of the main innovations in the proposed system of public order protection, which is implemented in the law enforcement activities of Ukraine as a “Scandinavian model”.